Partiti e gruppi parlamentari nell'ordinamento spagnolo - Salvatore, Curreri (Firenze University Press, 2005)
This volume represents the natural development of the theoretical conclusions which the author arrived at in a previous publication, devoted to the passage from the mandate prohibition to the party mandate. The analysis of the provisions present in the Spanish system as regards parties and Parliamentary groups, and in particular those aimed at countering the phenomenon of Parliamentary transfuguismo or switching, effectively confirms that it is possible to draw from the traditional principles on political representation meanings that better fit the peculiar role that the parties play within the current representative democracies, without undermining their foundations. Hence the necessity to define solutions of various kinds - constitutional, legislative, regulatory, conventional - designed to guarantee that the elected member respects the party mandate received from the voters.